The Effect of Work Environment and Motivation on Employee Performance Through Work Achievement at the Sub-District Office of Sipispis, Serdang Bedagai Regency - Ramadhini Safitri; Cut Sah Kha Mei Zsazsa; Saimah Rambe (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research was taken from the background of the initial problem, namely that the work environment can have an influence on performance, such as the room temperature being too hot and making employees who work feel hot so that employee comfort will decrease and poor room layout hinders employee movement, this hinders work performance. from there the need for strong motivation, this research was carried out to determine the influence of the work environment and motivation on employee performance through work performance at the Sipispis Subdistrict office, Serdang Bedagai Regency. The research used quantitative methods with research instruments to test the hypothesis. The population was 22 people and all were samples. 22 people because there are not enough of 100 people data analysis techniques classical assumption test, normality test, multicollinearity test, heterscedasticity, autecorrelation test and path analysis, with a tolerance value for variable X1 of 0.530, variable (X2) 0.530, variable (Z) 0.998, the value is greater than 0.10 . The results of the analysis of the value of tcount 2.118 > ttable 2.109, the significance value of the work environment (X1) 0.007 is smaller than 0.05 so that H1 in this study is accepted. The motivation variable (X2) has a significance value of 0.036 which is smaller than 0.05 and the t value is 3.339 > t table 2.109 so that H2 in the research is accepted. there is an influence of motivation (X2) on employee performance (Y). work performance (Z) found that the significance value was 0.000 < 0.05 and the tcount value was 5.888 < ttable 2.109 so that H5 in this study was accepted. The analysis results show that the tcount value is 12.268 > ttable 2.109 and the work environment significance value (X1) is 0.000, which is smaller than 0.05, so that H3 in this study is accepted. The influence of the work environment (X1) on work performance (Z). The motivation variable (X2) t value is 6.927 > t table 2.109 and the significance value of the work performance variable (X2) is 0.000 which is smaller than 0.05 so that the research H4 is accepted. The influence of motivation (X2) on work performance (Z). The results of the analysis of the significance value of X1 and So it is concluded that H6 of the research is accepted, namely that there is a simultaneous influence between work environment variables (X1) and motivation (X2) on employee performance variables (Y). The results of the analysis show that the significance value of X1 and It was concluded that H7 of the research was accepted, namely that there was a simultaneous influence between work environment variables (X1) and motivation (X2) on employee performance variables (Y) with work performance (Z) as the intervening variable.